Deep eutectic solvents cross‐linked molecularly imprinted chitosan microsphere for the micro‐solid phase extraction of p‐hydroxybenzoic acid from pear rind. Issue 2 (21st December 2020) - Li, Guizhen; Row, Kyung Ho
Abstract: A visual, rapid, and sensitive micro‐solid phase extraction method was developed for the detection of p ‐hydroxybenzoic acid using molecularly imprinted chitosan microspheres based on deep eutectic solvents, both as a functional monomer and template. The parameters were optimized by using the response surface methodology strategy. The extraction capacity of p ‐hydroxybenzoic acid from pear rind under the optimized conditions using response surface methodology was 46.32 mg/g, when the pH of the extract solution (2), extraction time (35 min), extraction temperature (30°C), and adsorbent dosage (2 mg). The molecularly imprinted chitosan microspheres produced higher selectivity and extraction capacity than the traditional materials.